Effect of Copolymer Latexes on Physicomechanical Properties of Mortar Containing High Volume Fly Ash as a Replacement Material of Cement - El-Sayed Negim; Latipa Kozhamzharova; Yeligbayeva Gulzhakhan; Jamal Khatib; Lyazzat Bekbayeva; Craig Williams (The Scientific World Journal)
This paper investigates the physicomechanical properties of mortar containing high volume of fly ash (FA) as partial replacement of cement in presence of copolymer latexes. Portland cement (PC) was partially replaced with 0, 10, 20, 30 50, and 60% FA. Copolymer latexes were used based on 2-hydroxyethyl acrylate (2-HEA) and 2-hydroxymethylacrylate (2-HEMA). Testing included workability, setting time, absorption, chemically combined water content, compressive strength, and scanning electron microscopy (SEM). The addition of FA to mortar as replacement of PC affected the physicomechanical properties of mortar. As the content of FA in the concrete increased, the setting times (initial and final) were elongated. The results obtained at 28 days of curing indicate that the maximum properties of mortar occur at around 30% FA. Beyond 30% FA the properties of mortar reduce and at 60% FA the properties of mortar are lower than those of the reference mortar without FA. However, the addition of polymer latexes into mortar containing FA improved most of the physicomechanical properties of mortar at all curing times. Compressive strength, combined water, and workability of mortar containing FA premixed with latexes are higher than those of mortar containing FA without latexes.